ظاهرة العنف ضد المرأة في الأندلس "نماذج مختارة" (Journal of the College of Basic Education, 2025)
Violence is a counter-action directed towards a person or thing, and the phenomenon of social violence in general or violence against women in particular, is a phenomenon that has its political, economic and social aspects. Andalusian women faced multiple cases of various types of violence, whether at the family level or in society. Violence reached several levels, sometimes reaching beating, insulting and killing. There is another type that we have seen through historical sources, which is sexual violence, and we will shed light on some cases of violence in Andalusian society.